The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1985
DOI: 10.1107/s0108270185009222
|View full text |Cite
|
Sign up to set email alerts
|

Structure of aquaoxo(N-salicylidene-L-alaninato)vanadium(IV)

Abstract: Abstract.[V(C t0H9NO3)O(HzO)], M r = 276.14, monoclinic, P2~, a= 8.514 (3), b= 7.394 (2), c= 9.210 (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

1987
1987
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 5 publications
1
15
0
Order By: Relevance
“…The coordination properties of Cu(I) ions, which form pseudotetrahedral complexes with bipyridine and phenanthroline ligands (15,(22)(23)(24), induce the organization of the oligobipyridine ligands BP2 and BP3. In the present complex, the three copper(I) centers have an almost identical, distorted tetrahedral coordination geometry.…”
Section: Resultsmentioning
confidence: 99%
“…The coordination properties of Cu(I) ions, which form pseudotetrahedral complexes with bipyridine and phenanthroline ligands (15,(22)(23)(24), induce the organization of the oligobipyridine ligands BP2 and BP3. In the present complex, the three copper(I) centers have an almost identical, distorted tetrahedral coordination geometry.…”
Section: Resultsmentioning
confidence: 99%
“…Crystal structures of Cu͑I͒ bis-phenanthroline complexes show deviations from an ideal tetrahedral geometry, with the two diimine ligands not exactly perpendicular. 7,26,27 It is however possible that intermolecular forces in a crystal are responsible for these deviations since proton nuclear magnetic resonance ͑NMR͒ spectra of these complexes in solution indicate equivalence of the two ligands on the NMR time scale at room temperature. 28 Lability of ligands in solution was experimentally observed 29 which indicates that the Cu͑I͒-L bond is not very strong resulting in presumably low harmonic frequency for the Cu͑I͒-L stretching motions.…”
Section: Introductionmentioning
confidence: 99%
“…In 1969 Theriot et al [35,36] reported the preparation of the first monomeric and dinuclear V IV O-N-salicylideneamino acidato complexes (later the dinuclear complexes were characterized as V V -containing compounds [105]) and in 1970 Fraústo da Silva and Gillard [5] the first V IV , V V and mixed valence N-salicylideneamino acidato complexes, as well as [V IV O(Sal-Gly)(py)] and [V IV O(Sal-Phe)(py)] (py = pyridine), the first complexes of this type containing coordinated N-heterocyclic ligands. This was followed by many studies involving vanadium-N-salicylideneamino acidato compounds, the 1st single crystal X-ray diffraction (XRD) study being published in 1985 with the structure of [V IV O(Sal-Ala)(H 2 O)] 1 [106] (Fig. 3).…”
Section: IV O-schiff Base Systems Derived From Amino Acidsmentioning
confidence: 99%